Study on Skin to Subarachnoid Space Depth of Pregnant and Nonpregnant Female in Cox's Bazar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: During the procedure of sub subarachnoid block the anaesthesiologist has to face the challange of insertion of spinocain needle puncluring the skin through the tissues upto the subarachnoid space. The skin of subarachnoid space depth (SSD) varies considerably at different levels of spinal canal. It also varies from patient tyo patient at the same level as per age, sex and body mass index in pregnant and non pregnant women. To measure the skin to SSD among Non-Pregnant and pregnant women in our population. To compare and to derive a formula for predicting SSD. Materials and methods: This prospective, observational study was carried out by the Department of Anesthesiology and Critical Care at Cox's Bazar Medical College Hospital from December 2021 to June 2022. Total of 224 female patients participated in this study. Non-pregnant women, and pregnant women were the two categories of patients. After doing a lumbar puncture, SSD (Subarachroid Space Depth) was measured. A method for predicting SSD was developed using statistical analysis, correlation, and study of the association between SSD and patient variables. Results: The mean SSD was 5.03±0.74cm. SSD was substantially higher in the pregnant group (4.54±0.47cm) than in the female non-pregnant sample (4.32±0.45cm). Conclusion: The SSD was dependent exclusively on BMI in both study groups. In our study, Craig's formula had the strongest correlation with the measured SSD. Key words: Lumbar puncture; Pregnant female; Subarachnoid space.Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 84-87